Safety and efficacy of cryolipolysis for non‐invasive reduction of submental fat - Kilmer, Suzanne L. (Lasers Surg Med, 2015)
BACKGROUND AND OBJECTIVES: Cryolipolysis has previously received FDA clearance for fat reduction in the abdomen, flanks, and thighs. There is also interest in small volume fat reduction for areas such as the chin, knees, and axilla. This article reports the results of a cryolipolysis pivotal IDE study for reduction of submental fullness. STUDY DESIGN/MATERIAL AND METHODS: A prototype small volume vacuum applicator (CoolMini applicator, CoolSculpting System, ZELTIQ Aesthetics) was used to treat 60 subjects in the submental area. At each treatment visit, a single treatment cycle was delivered at −10°C for 60 minutes, the same temperature and duration used in current commercially‐available cryolipolysis vacuum applicators. At the investigator's discretion, an optional second treatment was delivered 6 weeks after the initial treatment. The primary efficacy endpoint was 80% correct identification of baseline photographs by independent physician review. The primary safety endpoint was monitoring incidence of device‐ and/or procedure‐related serious adverse events. Secondary endpoints included assessment of fat layer thickness by ultrasound and subject satisfaction surveys administered 12 weeks after final cryolipolysis treatment. RESULTS: Independent photo review from 3 blinded physicians found 91% correct identification of baseline clinical photographs. Ultrasound data indicated mean fat layer reduction of 2.0 mm. Patient questionnaires revealed 83% of subjects were satisfied, 80% would recommend submental cryolipolysis to a friend, 77% reported visible fat reduction, 77% felt that their appearance improved following the treatment, and 76% found the procedure to be comfortable. No device‐ or procedure‐related serious adverse events were reported. CONCLUSION: The results of this clinical evaluation of 60 patients treated in a pivotal IDE study demonstrate that submental fat can be reduced safely and effectively with a small volume cryolipolysis applicator. Patient surveys revealed that submental cryolipolysis was well‐tolerated, produced visible improvement in the neck contour, and generated high patient satisfaction. These study results led to FDA clearance of cryolipolysis for submental fat treatment. Lasers Surg. Med. 48:3–13, 2016. © 2015 The Authors. Lasers in Surgery and Medicine Published by Wiley Periodicals, Inc.